Muscle MRI and functional outcome measures in Becker muscular dystrophy. Issue 1 (December 2017) - Barp, Andrea; Bello, Luca; Caumo, Luca; Campadello, Paola; Semplicini, Claudio; Lazzarotto, Annalisa; Sorarù, Gianni; Calore, Chiara; Rampado, Alessandro; Motta, Raffaella; Stramare, Roberto; Pegoraro, Elena
Abstract Becker muscular dystrophy (BMD) is a neuromuscular disorder allelic to Duchenne muscular dystrophy (DMD), caused by in-frame mutations in the dystrophin gene, and characterized by a clinical progression that is both milder and more heterogeneous than DMD. Muscle magnetic resonance imaging (MRI) has been proposed as biomarker of disease progression in dystrophinopathies. Correlation with clinically meaningful outcome measures such as North Star Ambulatory Assessment (NSAA) and 6 minute walk test (6MWT) is paramount for biomarker qualification. In this study, 51 molecularly confirmed BMD patients (aged 7–69 years) underwent muscle MRI and were evaluated with functional measures (NSAA and 6MWT) at the time of the MRI, and subsequently after one year. We confirmed a pattern of fatty substitution involving mainly the hip extensors and most thigh muscles. Severity of muscle fatty substitution was significantly correlated with specific DMD mutations: in particular, patients with an isolated deletion of exon 48, or deletions bordering exon 51, showed milder involvement. Fat infiltration scores correlated with baseline functional measures, and predicted changes after 1 year. We conclude that in BMD, skeletal muscle MRI not only strongly correlates with motor function, but also helps in predicting functional deterioration within a 12-month time frame.